On the effects of optimal implementation of variable rotor speed and power management on hybrid-electric rotorcraft - Saias, Chana Anna; Goulos, Ioannis; Pachidis, Vassilios; Bacic, Marko (American Society of Mechanical Engineers (ASME), 2023)
The concept of Variable Rotor Speed (VRS) has been recognized as an efficient means to improve rotorcraft operational performance and environmental impact, with electrification being a potential technology to further contribute to that. This paper explores the impact of optimal implementation and scheduling of VRS and power management strategy for conventional and hybrid-electric rotorcraft on energy, fuel, and emissions footprint. A multidisciplinary simulation framework for rotorcraft performance combined with models for engine performance and gaseous emissions estimation is deployed. A holistic optimization approach is developed for the derivation of globally optimal schedules for combined rotor speed and power split targeting minimum energy consumption. Application of the derived optimal schedules at mission level resulted to a 6% improvement in range capability for the VRS tilt-rotor relative to its conventional counterpart. For the hybrid-electric tilt-rotor, combined optimization of VRS and power management leads to an increase in range to 18.4% at 40% and 25% reduced payload for current (250 Wh/kg) and future (450 Wh/kg) battery technology, respectively. For representative Urban Air Mobility (UAM) scenarios, it is demonstrated that the VRS concept resulted in up to 10% and 14% reductions in fuel burn and NOX relative to the nominal rotor speed case, respectively. The utilization of the combined optimum VRS and power split schedules can boost performance with reductions of the order of 20%and 25% in mission fuel/CO2 and NOX at a reduced payload relative to the conventional tilt-rotor.
Keywords: urban air mobility; tilt-rotor; hybrid-electric propulsion; variable rotor speed; optimization; surrogate modeling; energy-management